Comparative Fishing Ability and Economic Efficiency of Mechanised Trawlers Operating Along the Kerala Coast - IYER, H. KRISHNA; RAJENDRAN, R.; CHOUDHURY, R. L. ROY (Fishery Technology, 1968)
This study was undertaken with a view to finding out the comparative fishing ability and economic performance of different fishing vessel sizes 9.15 m (30’), 9.76 m (32’) and 10.97 m (36’) designed by the Central Institute of Fisheries Technology and operating along the Kerala coast. Data were collected from selected vessels of these sizes for four consecutive fishing seasons from 1964-65 to 1967-68. The catch / unit effort and total effort per year for the 10.97 m (36’) vessels were much better than those for the 9.76m (32’) vessels. The yearly landings and the crew remuneration for the former were about twice those of the 9.76 m (32’) vessels. The economic efficiency of the 10.97 m (36’) vessels was also much better. The decline in landings per year in both size groups was more due to the reduction in the effort per year than the decline in catch / unit effort.